Peran Notaris Dalam Transaksi Pengadaan Tanah Untuk Lokasi Pembangunan Komplek Perkantoran Pemerintah Kabupaten Sekadau - Mochamad Elmo Sidiq; Asep Sunarsa; Amin Purnawan (Jurnal Akta, 2018)
ABSTRAKProblematik penelitian ini adalah : Apa dasar hukum  Peran Notaris dalam Transaksi Pengadaan Tanah Untuk Lokasi Pembangunan Komplek Perkantoran Pemerintah Kabupaten Sekadau? apa peran Notaris  Dalam Transaksi Pengadaan Tanah Untuk Lokasi Pembangunan Komplek Perkantoran Pemerintah Kabupaten Sekadau? dan apa akibat hambatan hukum atas Peran Notaris dalam Transaksi Pengadaan Tanah Untuk Lokasi Pembangunan Komplek Perkantoran Pemerintah Kabupaten Sekadau?Penelitian ini adalah dengan pendekatan yuridis-empiris yang bersumber dari pengumpulan data yang diperoleh dari data primer dan data sekunder, kemudian dianalisis dengan metode analisis kualitatif. Teknik pengumpulan data yang digunakan adalah teknik wawancara. Teknik analisis data menggunakan analisis data kualitatif.Hasil temuan peneliti menunjukkan bahwa Dasar hukum Notaris dan/atau PPAT dalam pertanahan, didasarkan pada Undang-Undang Nomor 30 Tahun 2004 tentang Jabatan Notaris dan Peraturan Kepala Badan Pertanahan Nasional Republik Indonesia Nomor : 1 Tahun 2006 tentang Ketentuan Pelaksanaan Peraturan Pemerintah Nomor : 37 Tahun 1998 tentang Peraturan Jabatan Pejabat Pembuatan Akta Tanah. Keputusan Presiden Nomor 55 Tahun 1993 maupun Peraturan Presiden Nomor 65 Tahun 2006, peralihan hak atas tanah tersebut dapat dilakukan melalui/dihadapan Notaris dan/atau PPAT. Peran nyata keterlibatan notaris dalam pembangunan komplek kantor Pemerintah Kabupaten Sekadau adalah pembuatan Akta Notaris Nomor 9 tanggal 06 Juli 2005 tentang Surat Perjanjian Pelepasan Hak atas Tanah di antara PT Sinar Bintang Sakti dan Pemda Kabupaten Sekadau dan Pembuatan Akta Notaris No. 10 tanggal 06 Juli 2005 tentang surat Pengakuan hutang yang pada pokoknya Pemkab Sekadau mengakui mempunyai hutang kepada CHAN INDRA, dengan jaminan tanah yang telah diterima pelepasan hak atas tanah dari CHAN INDRA selaku Direktur PT. Sinar Bintang Sakti. Perdebatan Notaris berwenang untuk membuat akta yang berkaitan dengan akta-akta pertanahan mengakibatkan keraguan mengenai keabsahan terhadap akta notaris yang terdapat dalam proyek pembangunan perkantoran di Pemerintah Kabupaten Sekadau.Kata Kunci : Notaris, Pengadaan Tanah, Kabupaten Sekadau. ABSTRACTIn relation to the authority of Notary, as mentioned in UUJN Number 30 Year2004 jo Law Number 2 Year 2014, Article 15 paragraph (2) letter (f), that Notary has authority to make deed related to land.The problematic of this research is: What is the legal basis of Notary's Role in Transaction of Land Procurement For Development Site of Sekadau Regency Government Complex  what is the role of Notary In Transaction of Land Procurement For Development Site of Sekadau Regency Government Complex ?; and what are the consequences of the legal barrier to the Notary's Role in the Land Acquisition Transaction for the Location of the Sekadau Regency Government Complex ?This research is with juridical-empirical approach that comes from collecting data obtained from primary data and secondary data, then analyzed by qualitative analysis method. Data collection techniques used are interview techniques. Data analysis techniques used qualitative data analysis.The findings of the researcher indicate that the legal basis of Notary and / or PPAT in the land is based on Law Number 30 Year 2004 regarding Notary Position and Regulation of the Head of National Land Agency Number 1 Year 2006 regarding Provisions on Implementation of Government Regulation Number 37 Year 1998 on the Regulation of Officials of the Establishment of Deed of Land. Presidential Decree No. 55/1993 and Presidential Regulation No. 65/2006, the transfer of land rights can be done through / in the presence of a Notary and / or PPAT. The real role of notary involvement in the construction of the Sekadau District Government office complex is the making of Notarial Deed No. 9 dated July 6, 2005 concerning Letter of Agreement on the Release of Land Rights between PT Sinar Bintang Sakti and the Regional Government of Sekadau Regency and the Notarial Deed. 10 dated July 6, 2005, concerning letters of recognition of debt principally Pemkab Sekadau acknowledged to have a debt to CHAN INDRA, with guaranteed land that has been received the release of land rights from CHAN INDRA as Director of PT. Sinar Bintang Sakti. The debate of a Notary is authorized to make deeds relating to land deeds lead to doubts about the validity of the notarial deed contained in office building projects in the Sekadau District Government.Suggestions to lawmakers to anticipate differences in legal interpretation in the future, it is recommended that both Law No. 30 of 2004 in conjunction with Law Number 2 Year 2014 on UUJN and the Notary Profession Code of Ethics, to strengthen the explanation of legislation has been compiled.Keywords : Notary Public, Land Procurement, Sekadau District.